"CORRECTIONAL AND DEVELOPMENTAL TECHNOLOGIES IN DEAF PEDAGOGY" (Proceedings of International Educators Conference, 2024)
In this article, early identification and initiation of correctional and developmental work with children from birth to 3 years will significantly reduce the risk of manifestations of developmental disorders at an older age. Correctional and developmental work with children and adolescents is a very important area of activity not only for teachers, but also for psychologists and social educators. It must be carried out systematically and built on a scientific basis.